HUBUNGAN KEMAMPUAN MEMBACA DENGAN PRESTASI BELAJAR BAHASA INDONESIA SISWA KELAS VI SD NEGERI 125543 PEMATANG SIANTAR - Cindy Pricilia Sitompul (ADIBA : JOURNAL OF EDUCATION, 2025)
Reading is important so that we can understand the reading and be able to describe it. To be able to understand the content of reading language students must often understand the book being read, identify the content of the book, find new knowledge that has not been known before, and be able to understand the intention of the author of the book. The research was written with a correlational design based on the percentage of results from the acquisition of research on the relationship of reading ability in learning achievement Indonesian grade VI students at UPTD SDN 125543 Pematangsiantar. This shows that the reading ability of elementary school students at UPTD SD Negeri 125543 Pematang Siantar is included in the good category because it shows that the frequency is the most. Based on information, the results of research and discussion show a significant correlation between reading ability and learning achievement Indonesian grade VI at UPTD SD Negeri 125543 Pematang Siantar in the 2023/2024 school year. The magnitude of the relationship between the variables of reading ability and the learning process Indonesian 0.3691. At the significance level of 0.05, the results of 0.3691 > 0.3494 were obtained, so it can be concluded that there is a significant correlation between the two variables. So if students have a high reading point then the achievement of learning Indonesian.